(untitled) (Agroindustrial Science, 2020)
Milk is a food that has a great importance in society because, for its commercialization, payment for quality is used, where the physical-chemical and microbiological parameters determine the price of milk. Therefore, the objective of this research was to determine the influence of environmental factors (temperature, rain precipitation, humidity, solar radiation) on the physicochemical and microbiological quality of bovine milk in the zones of the San Martín Region - Peru. For it samples of milk were gathered in every zone of study and were analyzed to obtain his characteristics of density, acidity, fat, protein, solid total, aerobic mesophiles and numbering of coliforms. Duncan test at 5% was used to compare means, in addition Spearman correlation was performed in order to determine the degree of association between the variables of physicochemical and microbiological quality of milk with environmental factors. Concluded that environmental factors affect the density, fat and thus in the number of total solids in milk. Besides environmental factors directly affecting the numbering of aerobic mesophilic, especially solar radiation and temperature.